Hexokinase II may be dispensable for CD4 T cell responses against a virus infection - Varanasi, Siva Karthik (PLoS One, 2018)
Activation of CD4 T cells leads to their metabolic reprogramming which includes enhanced glycolysis, catalyzed through hexokinase enzymes. Studies in some systems indicate that the HK2 isoform is the most up regulated isoform in activated T cells and in this report the relevance of this finding is evaluated in an infectious disease model. Genetic ablation of HK2 was achieved in only T cells and the outcome was evaluated by measures of T cell function. Our results show that CD4 T cells from both HK2 depleted and WT animals displayed similar responses to in vitro stimulation and yielded similar levels of Th1, Treg or Th17 subsets when differentiated in vitro. A modest increase in the levels of proliferation was observed in CD4 T cells lacking HK2. Deletion of HK2 led to enhanced levels of HK1 indicative of a compensatory mechanism. Finally, CD4 T cell mediated immuno-inflammatory responses to a virus infection were similar between WT and HK2 KO animals. The observations that the expression of HK2 appears non-essential for CD4 T cell responses against virus infections is of interest since it suggests that targeting HK2 for cancer therapy may not have untoward effects on CD4 T cell mediated immune response against virus infections.